IFAS Community Development: Empowering Your Community, Stage 3, Goal Setting and Strategy Formulation - Mark A. Brennan (EDIS, 2005)
This paper is part of a series of discussions on community development. This series includes specialized papers on civic engagement, community action, and other topics important to the development of community. This document is FCS9228, one of a series of the Family, Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 2005.